Integration of newly arrived immigrant pupils into schools : focus ethnography on 'preparation for basic education' in Finland - Djabanor, Jerry (2016)
The research analyses a unique approach of everyday life experiences of newcomers in relation to their initial education towards mainstream schooling. The aim of the research was to find out how pupils’ gets motivated towards Finnish language learning skills and how social life integration impact on pupils’ initial education as they navigate their pathways in their new environment. The research focused on observation, artistic, pencil and paper diary, and interaction method of approach in triangulating those everyday life experiences into perspective. An audio-recorder, vignettes, and packet-notes were used for the data gathering processes. The analyses of the research were based on grounded theory approach (see Glaser & Strauss, 1967; Glaser, 1992; Glaser, 1978) where patterns of the generated data sets as well as the interrelationship of the data sets were scrutinized by conceptual description and comparative techniques and a theory driven approach as in background literature where data sets were related to previous concepts or theories. The outcome of the research suggests combination of multiple factors that impact on newcomers’ initial education. These include; possibilities of establishing friendship with native peers, issues of self confidence, impact of second generation immigrant peers, the effects of teaching and learning methods, the role of teachers and parents motivational guidance, and limited places for the organization of the program and its effects. The outcome of this research are significant for social workers, language researchers, and teachers who play essential role in building their learners’ self-confidence and willingness to communicate, both within and outside the classroom.